Kajian Kelayakan Potensi Energi Angin Untuk Dimanfaatkan Menjadi Energi Listrik Disekitaran Legok - Kota Jambi - Leily W Johar (Journal of Electrical Power Control and Automation (JEPCA), 2018)
Electrical energy is one of the needs that can not be separated from human life in general. The demand for electrical energy over time is increasing, for which an unlimited source of renewable energy availability in nature needs to be developed to meet the needs of electrical energy. In the city of Jambi and its surroundings, the state of the territory is covered by a stream of batanghari river flow and extensive field conditions, free from the wind barriers both the trees and buildings for which this condition is required to undertake more in-depth research studies of wind power, using wind speed data at a certain height allows for the availability of electrical energy. In this study the location to determine the parameters of wind energy is in the city of Jambi with geographic position at coordinates 1.59,103,600-219, this study uses explorative survey method by conducting direct measurement in the field, this study aims to determine the potential of wind energy that can be converted into electrical energy, how decent wind speed conditions in the city of Jambi to be utilized into electrical energy. From the data obtained, the average wind speed in a year using primary data at 2 meters from the batanghari river edge is 2.45 m / s and the maximum effective power produced by the windmill assuming the 4 m2 cross-sectional area is 374.68 Watt which occurs in July, when applied to the Micro Wind Turbine Z - 400W [5] specification can generate electrical energy, but the resulting electrical energy capacity is very small.